Алманың әр түрлі генотиптерін in vitro клондауды оңтайландыру (Experimental biology, 2020)
At each stage of plant clonal micropropagation appear difficulties, such as a failed sterilization, poor reproduction, abnormal development of microplants and phenolic oxidation plants in a nutrient medium. The consequences of such failures can lead to plant necrosis, and sometimes death. Successful micropropagation of plants depends on several internal and external factors, including ex vitro and in vitro conditions. It is important to create optimal conditions at each stage of micropropagation to achieve a high multiplication coefficient of in vitro plants. The article presents the results of improving the technology of clonal micropropagation of apple plants at different stages. Experiments conducted have shown that apple shoots are effectively sterilized with 0,2% HgCl2 at an exposure of 4 min. In this case, the number of explants capable of regenerating is 76% for variety Golden Delicious, 85% for variety Voskhod, 75% for variety Maksat. The best medium for isolating explants is MS medium containing double amount of iron chelate; vitamin C -1.5 mg/l; polyvinylpyrralidone - 250 mg/l; glycine - 2 mg/l; BAP - 0.5 mg/l; The IMC is 0.1 mg/l, 79% of regenerating apple shoots were obtained with such a composition of the nutrient medium. The optimal medium for micropropagation of apple is the mineral basis of MS with a hormonal composition: 1.0 mg/l BAP, 0.1 mg/l IMC, 0.1 mg/l HA. The multiplication coefficient of the studied cultivars ranged from 4 to 13 depending on the genotype. 36 cultivars and 9 wild forms of apple are introduced into in vitro culture and propagated.Key words: clonal micropropagation, in vitro, sterilization, nutrient medium, apple.